2020
DOI: 10.1002/ejp.1533
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided continuous deep serratus anterior plane block versus continuous thoracic paravertebral block for perioperative analgesia in videoscopic‐assisted thoracic surgery

Abstract: Background The deep serratus anterior plane block (SAPB) is a promising novel regional anaesthesia technique for blockade of the anterolateral chest wall. Evidence for the efficacy of SAPB versus other analgesic techniques in thoracic surgery remains inadequate. Aims This study compared ultrasound‐guided continuous SAPB with a surgically placed continuous thoracic paravertebral block (SPVB) technique in patients undergoing videoscopic‐assisted thoracic surgery (VATS). Methods In a single‐centre, double‐blinded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 33 publications
1
56
0
3
Order By: Relevance
“…Qiu et al 11 also confirmed asimilar effect of SAPB and PVB in terms of postoperative acute pain, additional analgesia, postoperative nausea and vomiting, pain assessment at rest and on coughing, without any significant difference. Hanley et al 12 found that continuous SAPB provided better postoperative 24-hour NRS assessment of rest pain, coughing pain, and movement pain, compared with continuous PVB. The results of our study show that cSAPB significantly relieved the pain of patients at rest, which is similar to the results of the previous studies.…”
Section: Figurementioning
confidence: 99%
“…Qiu et al 11 also confirmed asimilar effect of SAPB and PVB in terms of postoperative acute pain, additional analgesia, postoperative nausea and vomiting, pain assessment at rest and on coughing, without any significant difference. Hanley et al 12 found that continuous SAPB provided better postoperative 24-hour NRS assessment of rest pain, coughing pain, and movement pain, compared with continuous PVB. The results of our study show that cSAPB significantly relieved the pain of patients at rest, which is similar to the results of the previous studies.…”
Section: Figurementioning
confidence: 99%
“…33 Hanley et al have shown that SAPB is a non-inferior regional anesthesia technique in terms of analgesic efficacy compared to PVB when incorporated within a multimodal analgesia regimen. 16 In our study, patients in the D2 group had a significantly lower VASr score (during the first 24 h after surgery) and opioid requirement after surgery; however, the prevalence of chronic pain and functional measures were similar between the two groups. Khalil et al reported that SAPB maintained hemodynamic stability compared with TEB and led to lower pain scores and less morphine consumption in the early postoperative period after thoracotomy, with no noteworthy complications.…”
Section: Discussionmentioning
confidence: 42%
“…All patients had a standardized postoperative multimodal analgesia regimen including 1 g oral paracetamol and 400 mg oral ibuprofen every 8 h based on the previous study. 16 If the visual analog scale for pain while coughing (VASc) score was ≥4, 2.5 µg intravenous sufentanil was given.…”
Section: Anesthesiamentioning
confidence: 99%
“…At the end of this study, they reported that SAPB blocks only the lateral cutaneous branches of the intercostal nerves; therefore, further studies are needed on the analgesic activity of SAPB. While studies on the activity of SAPB continue, Hanley et al 27 published a very recent study. In two groups of 20 patients who underwent VATS, they performed continuous deep SAPB on one group while performing continuous paravertebral block on the other; this study reported preferring deep SAPB as this avoids the need for a long thoracic nerve block.…”
Section: Discussionmentioning
confidence: 99%